Korelasi Perkembangan Industri Otomotif terhadap Dinamika Istilah dalam Bahasa Indonesia : Penelitian - Cavin Ananda Teguh S; Tri Indah Prasasti; Yanuardi Gulo; Sigit Hafiz Pranata; Naufal Zuhri Siregar; Herman Fazri Napitupulu; Muhammad Raihan Alfandi Simanjuntak (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The development of the automotive industry in Indonesia has significantly influenced the emergence and development of new terms in the Indonesian language. This dynamic is characterized by the adoption of foreign vocabulary, the adaptation of technical terms, and the creation of equivalents that comply with Indonesian language rules. This article aims to examine the correlation between the growth of the automotive industry and the changes, absorption, and adaptation of terms in the Indonesian language. The methods used are literature studies and observations of terms used in the media, education, and the automotive industry. The results of the study indicate that the more advanced the automotive industry, the morenew terms enter and develop in the Indonesian language. This demonstrates that the automotive industry influences not only the economic and technological fields, but also the development of the